Anti-Tumor Effects of Carrimycin and Monomeric Isovalerylspiramycin I on Hepatocellular Carcinoma in Vitro and in Vivo - Jin, Yong; Zuo, Hong Xiang; Li, Ming Yue; Zhang, Zhi Hong; Xing, Yue; Wang, Jing Ying; Ma, Juan; Li, Gao; Piao, Hongxin; Gu, Puqing; Jin, Xuejun (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma results in a high risk of second primary malignancies and has prominent morbidity and mortality. There is a lack of effective treatment and prognosis is poor. Therefore, effective drugs need to be discovered. Carrimycin is a 16-member macrolide antibiotic with anticancer activity, and monomeric isovalerylspiramycin I is a main component. The aim of this study was to determine the anti-tumor effects of carrimycin and monomeric isovalerylspiramycin I on hepatocellular carcinoma through in vivo and in vitro experiments. In vitro, changes in cellular proliferation, migration, invasion, and apoptosis were analyzed by MTT, colony formation, EdU labeling, wound-healing, matrigel transwell invasion, and flow cytometric assays using SK-Hep1, Hep3B, SNU-354, SNU-387 hepatocellular carcinoma cell lines. Western blotting and RT-PCR were used to detect the effects of carrimycin and monomeric isovalerylspiramycin I on the expression levels of vascular endothelial growth factor (VEGF) and programmed death ligand 1 (PD-L1). Nude mice were subcutaneously transplanted with SK-Hep1 cells or C57BL/6J mice were orthotopically transplanted with hepatocarcinoma H22 cells. Tumor volume, pathological changes in tumor tissues, and the concentration of VEGF in mouse serum were measured after treatments. Carrimycin and monomeric isovalerylspiramycin I dose-dependently inhibited hepatocellular carcinoma cell viability, colony formation, and DNA replication. These agents markedly suppressed migration and invasion and promoted apoptosis of the cell lines. Western blotting and RT-PCR demonstrated that carrimycin and monomeric isovalerylspiramycin I reduced VEGF and PD-L1 protein and mRNA levels in a dose-dependent manner. In vivo studies further confirmed that carrimycin and monomeric isovalerylspiramycin I could significantly inhibit tumor growth, tumor histopathological alterations, and the concentration of VEGF in both mouse tumor models. These results show that carrimycin and monomeric isovalerylspiramycin I promoted apoptosis and inhibited proliferation, migration, and invasion of hepatocellular carcinoma cells. Therefore, our discovery suggests anti-tumor capacity for carrimycin and monomeric isovalerylspiramycin I and provides data on potential new drugs for inhibiting hepatocellular carcinoma.